Temporomandibular disorder and dysfunctional breathing - Eliane C. Rodrigues Corrêa; Fausto Bérzin (Universidade Estadual de Campinas, 2015)
This article studied the relationship among respiratory, masticatory and cervical muscles and the factors that contribute for TMD. It consists in a review of studies approaching dysfunctional breathing and TMD, enclosing mouth breathing syndrome, anxiety, respiratory mechanics changes, diaphragmatic muscular dystonia and overuse of accessory inspiratory muscles. It also stresses the importance of breathing evaluation and the multiprofessional intervention in the TMD patients.